Pengaruh Kombinasi Jenis Pupuk Terhadap Tanaman Kedelai (Glycine max L. Merrill) Varietas Grobogan - Adam Imtinan Laqin; Vera Vera Oktavia Subardja; Wagiono Wagiono (UNIVERSITAS LABUHANBATU, 2026)
Soybeans (Glycine max L. Merrill) are nicknamed Gold from the soil, which contributes to the provision of nutritious food. Soybeans are the most important staple food crop after rice and corn. The increase in national soybean demand is not matched by an increase in national soybean production. Domestic soybean production is only able to meet around 65.61% of domestic consumption. Efforts to increase soybean production through intensification and extensification of technical efficiency in soybean cultivation, namely organic fertilization. This study aims to obtain the best combination dose of goat manure, formula 100+ biofertilizer and formula 100+ liquid organic fertilizer for the growth and yield of soybean plants. The study was conducted in the village of Telukjambe Timur, Puseurjaya, Karawang Regency. The method used is an Experiment with a single factor Randomized Block Design with 6 treatments and 6 replications, consisting of: P1 (0.15 l/ha liquid organic manure), P2 (0.15 l/ha liquid organic manure + 5 tons/ha goat manure), P3 (0.15 l/ha liquid organic manure + 20 l/ha biological manure), P4 (0.15 l/ha liquid organic manure + 20 l/ha biological manure + 5 tons/ha goat manure), P5 (5 tons/ha goat manure), P6 (20 l/ha biological manure + 5 tons/ha goat manure). so that there are 24 experimental units. The data obtained were analyzed by the F test at a level of 5% with further testing by the Duncan Multiple Range Test (DMRT). The results showed that there was a significant effect of the combination of fertilizer types, namely goat manure + biological manure + liquid organic manure (POC), on the growth and yield of Grobogan variety soybean plants. For parameters such as plant height, number of leaves, root length, total number of pods, number of filled pods, dry weight of 100 seeds, number of seeds per plant, and seed weight per plant, the best treatment was obtained with a combination of Liquid Organic Mature (0.15 l/ha) and Biofertilizer (20 l/ha) (treatment P3). This treatment provided the best vegetative and generative growth results. Keywords: soybean, goat mature, liquid organic mature, biological mature